Evaluation of the Therapeutic Effects of the Hydroethanolic Extract of Portulaca oleracea on Surgical-Induced Peritoneal Adhesion. (2nd August 2021) - Jaafari, Ali; Baradaran Rahimi, Vafa; Vahdati-Mashhadian, Nasser; Yahyazadeh, Roghayeh; Ebrahimzadeh-Bideskan, Alireza; Hasanpour, Maede; Iranshahi, Mehrdad; Ehtiati, Sajjad; Rajabi, Hamed; Mahdinezhad, Mohammadreza; Rakhshandeh, Hassan; Askari, Vahid Reza
Abstract : Objective . Peritoneal adhesion (PA) is an abnormal connective tissue that usually occurs between tissues adjacent to damaged organs during processes such as surgery. In this study, the anti-inflammatory and antioxidant effects of Portulaca oleracea (PO) were investigated against postoperative-induced peritoneal adhesion. Methods . Thirty healthy male Wistar rats (220 ± 20   g, 6-8 weeks) were randomly divided into four groups: (1) normal, (2) control (induced peritoneal adhesion), and (3) and (4) PO extracts (induced peritoneal adhesion and received 100 or 300 mg/kg/day of PO extract for seven days). Finally, macroscopic and microscopic examinations were performed using different scoring systems and immunoassays in the peritoneal lavage fluid. Results . We found that the levels of adhesion scores and interleukin- (IL-) 1 β, IL-6, IL-10, tumour necrosis factor- (TNF-) α, transforming growth factor- (TGF-) β 1, vascular endothelial growth factor (VEGF), and malondialdehyde (MDA) were increased in the control group. However, PO extract (100 and 300 mg/kg) notably reduced inflammatory (IL-1 β, IL-6, and TNF- α ), fibrosis (TGF- β 1 ), angiogenesis (VEGF), and oxidative (MDA) factors, while increased anti-inflammatory cytokine IL-10, antioxidant factor glutathione (GSH), compared to the control group. Conclusion . Oral administration of PO improved postoperational-induced PA by alleviating the oxidative factors, fibrosis, inflammatory cytokines, angiogenesis biomarkers, and stimulating antioxidative factors. Hence, PO can be considered a potential herbal medicine to manage postoperative PA. However, further clinical studies are required to approve the effectiveness of PO.